(untitled) (Cambridge, 2001)
This concise but wide-ranging handbook reviews the epidemiology of neurological disease and the treatment and prognosis of all major diseases of the nervous system.
Keywords: Nervous system diseases,Neurology,Epidemiologic methods,Hệ thống bệnh thần kinh,Thần kinh học,Phương pháp dịch tễ học; Epidemiology,Dịch tễ học